(untitled) (Palíndromo, 2019)
The article presents artistic and pedagogical landscapes that reflect on aesthetic education, unfolded in experiences and cartographic movements present in the works of the Research Group [Between] Landscapes, CNPq / UDESC. This is constituted of two Lines of Research, the first investigating the process of creation in Art, and the se-cond the process of creation in Art and Education, proposing to reconfigure other landscapes in visual arts formations, both undergraduate and baccalaureate. The purpose of the group is to promote articulations between teacher education and poetic formation in order to highlight their relational aspect. Thus, the article presents some of these landscapes designed by the projects anchored in the GP, in which each researcher investigates different conceptions and theoretical axes that intersect with philosophy.